Prediction of Outcome in Acute Hemorrhagic Stroke from Initial Clinical Presentation and a Single CT Scan on Admission - Hossain, Md Motahar; Habibullah, Mohammad; Hasan, Abu Mohammad Shafiqul; Alam, Md Mahbubul; Rahman, Shafiqur; Rumee, Sharif Mahmud (Journal of Dhaka National Medical College & Hospital, 2017)
Background: Intracerebral hemorrhage (ICH) accounts for about 7-15% of all strokes and is the most devastating type of stroke with mortality rate of 34%-51% Objective: The study was done to determine the potential prodictors for short-term mortality and neurological recovery in ICH patients by clinical and computed tomographic (CT) correlation. Methods: This study was conducted over 100 admitted patients out of them fifty were diabetic, in the department of Medicine, Sher-E-Bangla Medical College Hospital, Barisal, Bangladesh for a duration of one year from 01.07.2010 to 30.06.2011. Data was collected in hospital directly from patient or attendance. Result was calculated using Chi-square test. Result: In this study mean age of the ICH patients was 60.26 ± 11.22 years. The clinical and CT scan findings were correlated with the outcome. GCS score was significantly higher among survivors. Poor outcome was associated with a hematoma volume of more than 30ml and presence of ventricular extension. Mortality of hemorrhagic stroke patients was 40% in first month. Most of the death occurred in first 7 days. Conclusion: Though outcome and functional status at discharge were well correlated with the initial CT scan findings, age and GCS score, but larger study with greater matched variables, risk factors and long-term follow-up is needed to make a concrete comment. J. Dhaka National Med. Coll. Hos. 2017, 23 (02): 28-32